Leonico Tomeo’s Marginalia: Manuscript and Print in Sixteenth-Century Veneto - Steenson, Allison (Library, 2023)
Abstract This article centres on a connection between the manuscript reading marks of the Italian humanist Niccolò Leonico Tomeo (Venice 1456-Padua 1531), in the form of curved branches with sprouting leaves, and printed marginal notes found in early editions of his works printed in Venice and Paris. Known generally as a Greek scholar of Aristotle active at the University of Padua, Leonico had also an important role in contemporary intellectual and political debate, especially in relation to his many close English acquaintances. This article examines the occurrences of these unique marginal annotations in manuscript and print, and connects Leonico’s printed works to the printing and intellectual environment in Padua and Venice.